2002
DOI: 10.1080/090647002762381104
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Milk Production in Lactating Sows by Determination of Deuterated Water Turnover in Three Piglets per Litter

Abstract: Estimation of milk production in lactating sows by determination of deuterated water turnover in three piglets per litter.The milk intake in piglets from four lactating sows was measured in three 48 h periods, starting on days 3, 10 and 17 of lactation, using the deuterium oxide (D 2 O) dilution technique. The milk intake was estimated from the water turnover in the piglets corrected for the production of metabolic water. The water turnover was estimated from the water dilution space and the fractional turnove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 22 publications
(38 reference statements)
4
66
1
Order By: Relevance
“…According to our previous study (Theil et al, 2002), the BWF of sucking piglets decreases curvilinearly with increasing LW and may be predicted by BWF pred ðwith no unitÞ…”
Section: Analysesmentioning
confidence: 88%
See 4 more Smart Citations
“…According to our previous study (Theil et al, 2002), the BWF of sucking piglets decreases curvilinearly with increasing LW and may be predicted by BWF pred ðwith no unitÞ…”
Section: Analysesmentioning
confidence: 88%
“…Since the costs of DLW (especially 18 O water) are significant, only three piglets per litter were enriched with DLW. In a previous study, we showed that determination of milk intake of three sucking piglets per litter was sufficient to estimate the milk intake of the whole litter and thereby the milk production of the sow (Theil et al, 2002). In four of eight litters, piglets that were not enriched with DLW were labelled with D 2 O to determine milk intake.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations